Leitura literária na sala de aula: idas e vindas, interações e descobertas - Souza, Roselene Maria Santana e (2022)
Innovations in technology have seemingly contributed to keep students away from literary books and, as a consequence, from the reading habit and as one may verify in library record books which have been examined in two first-stage schools of elementary education (Ensino Fundamental) in the city of Inhumas, Goiás. It has been found that fifth-grade students are the ones who have borrowed the fewest books. Such a circumstance tends to get worse in subsequent grades, a fact which may increase the number of students in the late grades of primary education who feel discouraged concerning reading, even though it is an important criterion for good academic performance. This project takes that perspective into consideration and aims to help develop literary readers who are attracted and committed to the practice of reading in the school. The research has been theoretically based on the studies of Todorov (2009), Coelho (2000), Cosson (2012, 2014 and 2019), Zilberman (1988), Colomer (2003 and 2007), Cademartori (1986, 2009, 2012), Candido (1995), Andruetto (2017), among others. The methodology includes the creation of a reference readers group in order to promote reading practices in an associate school. The inquiry has targetted a group of fifth graders of a reference school who integrate a "Literary Readers Group", and a group of fifth graders who study either in the morning or in the afternoon at an associate school in Inhumas and constitute the "Reading Development Group". The proposition is a practical experiment with literary books that has been carried out by a literary reading project. It focuses on a set of activities which enhance the process of literary readers practice and culminated in the educational product, a documentary video called Projeto de Leitura Literária: Entre Idas e Vindas, um Ato de Prazer (Literary Reading Project: Between Comings and Goings, an Act of Pleasure), developed during the Professional Master's in Teaching in Basic Education of the Stricto Sensu Postgraduate Program at CEPAE/UFG. The product is available at the link: https://youtu.be/Eu-jhvB6sJI.